1997
DOI: 10.1002/(sici)1097-4601(1997)29:2<149::aid-kin9>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the rate constants of the reactions of oxygen atoms with 1‐pentene, 1‐hexene, cis‐2‐pentene, and trans‐2‐pentene

Abstract: The kinetics of the reactions of ground state oxygen atoms with 1-pentene, 1-hexene, cis-2-pentene, and trans-2-pentene was investigated in the temperature range 200 to 370 K. In this range the temperature dependences of the rate constants can be represented by k ϭ AЈ T n exp(Ϫ E a Ј/RT) with AЈ ϭ (1.0 Ϯ 0.6) и 10 Ϫ14 cm 3 s Ϫ1 , n ϭ 1.13 Ϯ 0.02, E a Ј ϭ 0.54 Ϯ 0.05 kJ mol Ϫ1 for 1-pentene; AЈ ϭ (1.3 Ϯ 1.2) и 10 Ϫ14 cm 3 s Ϫ1 , n ϭ 1.04 Ϯ 0.08, E a Ј ϭ 0.2 Ϯ 0.4 kJ mol Ϫ1 for 1-hexene; AЈ ϭ (0.6 Ϯ 0.6) и 10 Ϫ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…Also, the bond formed by OH addition to alkenes is not unusually strong, with the addition being reversible at the relatively low temperature of 500 -600 K. 51 Similarly, radical atoms are know to undergo barrierless addition to alkenes, [52][53][54] this is consistent with the above explanation for hydroxyl, as they are of even higher symmetry than OH. …”
Section: 23supporting
confidence: 81%
See 1 more Smart Citation
“…Also, the bond formed by OH addition to alkenes is not unusually strong, with the addition being reversible at the relatively low temperature of 500 -600 K. 51 Similarly, radical atoms are know to undergo barrierless addition to alkenes, [52][53][54] this is consistent with the above explanation for hydroxyl, as they are of even higher symmetry than OH. …”
Section: 23supporting
confidence: 81%
“…Indeed, hydroxyl radicals are not unusually electrophilic; the energy released by charge transfer by addition to alkenes (ranging from 19 kJ mol -1 for ethene to 40 kJ mol -1 for 2,3-dimethyl-2-butene) is comparable with the range found for peroxyl radicals (3-33 kJ mol -1 ). Also, the bond formed by OH addition to alkenes is not unusually strong, with the addition being reversible at the relatively low temperature of 500-600 K. 51 Similarly, radical atoms are known to undergo barrierless addition to alkenes; [52][53][54] this is consistent with the above explanation for hydroxyl, as they are of even higher symmetry than OH. The reactions of three other triatomic or larger species with alkenes have been examined extensively (difluoroamino (NF 2 55,56 ), nitrate (NO 3 [57][58][59] ), and ozone (O 3 60,61 )); they do have appreciable activation energies and also show strong correlations with the ionization energies of the alkenes, again indicating electrophilic addition.…”
Section: The Mechanism Of the Addition Of Peroxyl Radicals To Alkenesmentioning
confidence: 52%
“…The problem addressed in this paper has been treated by F. Stuhl and co-workers in a different way. [7][8][9] They observed that the Arrhenius plot of ln k vs 1/T was strictly linear for ethylene but was slightly bent for monoalkylethenes. The plot was fitted to a sum of two terms of the form A exp(-E a /RT), one for each reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Many radical−molecule reactions exhibit negative activation energies, with their rate coefficients decreasing with increasing temperature, even in the high-pressure limit. For example, negative activation energies have been noted for a wide variety of olefin reactions with Cl atoms, with O( 3 P) atoms, and with hydroxyl radicals . The role of negative activation energies has also been widely discussed in the reactions of hydrocarbon radicals with hydrogen halides and the related reverse reactions. …”
Section: Introductionmentioning
confidence: 99%